Revisiting Fiscal Transfer Equity: Lessons from Indonesia’s General Allocation Fund Reform - Abdul Chalid Ahmad; Chairullah Amin; Said Mala; Irawan Abae (Amkop Management Accounting Review (AMAR), 2026)
Indonesia's fiscal transfer system predominantly relies on a formula-based approach, which tends to reflect continental characteristics and neglects the unique needs of archipelagic regions. As a result, provinces with extensive marine territories are structurally disadvantaged in the allocation of General Allocation Funds (GAF), Special Allocation Funds (SAF), and Revenue Sharing Funds (RSF). In response to this disparity, a policy was introduced in 2018 to incorporate a 100% weight for marine area in the GAF formula; however, no parallel adjustments have been made for SAF or RSF. This study investigates the impact of this reform, along with other determinants, on fiscal transfer disparities and regional inequality between archipelagic and non-archipelagic provinces over the period 2012–2023. Using panel data and a fixed-effects model, the findings indicate that higher GRDP per capita significantly reduces disparities in per capita GAF, SAF, and RSF. In contrast, local government revenue per capita exacerbates these disparities. Additionally, regional fiscal dependency and the 2018 reform are found to worsen per capita GAF disparities. On the other hand, the ratio of GAF, SAF, and RSF to regional direct expenditures, the ratio of Own-Source Revenue (OSR) to total expenditure, and the GAF reform contribute to reducing regional income inequality. Among these, OSR ratios and GRDP per capita exhibit the strongest equalizing effects. These results underscore the importance of differentiated transfer formulas that account for regional typologies, particularly in archipelagic contexts.